Drylands offer possibilities, not just problems - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Good Practices in Drylands Management. R Øygard, T Vedeld and J Aune. Noragric World Bank co-publication. 1999. 116 pp. Free of charge The Library, Noragric PO Box 5001 1432 As, Norway Fax +47 64 94 07 60 Email: library.noragric@nlh.no